Oxigenoterapia de alto flujo y su influencia en pacientes de 18 a 70 años con insuficiencia respiratoria del área de cuidados intensivos Hospital IESS Babahoyo periodo octubre 2019-marzo 2020. - Mendoza Guerrero, Maria Isabel (2020)
This research work is based on high-flow oxygen therapy and its influence on patients aged 18 to 70 years with respiratory failure in the intensive care area, whose objective is to determine the influence of high-flow oxygen therapy on patients with respiratory failure with the sole purpose of determining their quality of life. In order to carry out this research work, clinical histories of the patients admitted to the intensive care unit were used, in addition in its methodology the deductive method is used accompanied by a quantitative modality, it is of a basic, descriptive, correlational type, the population is composed of young adult and older adult patients hospitalized with concomitant diseases that trigger respiratory failure whose data were collected through medical records which resulted in 60% of admitted patients being older adults to whom pneumonia with a 34% is the concomitant disease with greater enhancement and the tests performed as arterial gasometry the predominant alteration is respiratory acidosis with 50% also resulting in 70% of patients with respiratory failure who are under the high flow system respond in a beneficial way to the PaO2 relationship / FiO2 (Pafi) as it is a predictive for the onset and weaning of high flow oxygen therapy in a patient with this condition. It is concluded that oxygen therapy does exert a great influence on patients with respiratory failure at the IESS hospital in Babahoyo.